ANALISIS GAIRAIGO YANG TERDAPAT DALAM MEDIA CETAK YOMIURI SHINBUN - Kania, Fanny Dwi; Supriatnaningsih, Rina; Wardhana, Chevy Kusumah (Chi'e: Journal of Japanese Learning and Teaching, 2018)
This paper describes the process of forming the word on Gairaigo. Gairaigo is a Japanese loanword which originates from a foreign language except Chinese. It undergoes sound adjustments (Phonology) and grammatical adjustments before being borrowed and used as Gairaigo in Japanese. Gairaigo analyzed is gairaigo which was written in Yomuiri Shinbun Newspaper, edition of 22nd of January 2017. There are two processes which occur on Gairaigo existing in the data source. Firstly, the phonological process or sound adjustment is divided into 5 aspects. They are Adding vocals, changing sounds, accents, and pronunciations according to the spelling. Secondly,the Morphological process or the word-former morpheme. The morphological process is divided into 2; Fukugo (compound) and Ryakugo (Abbreviation). Ryakugo consists of abbreviation, clipping, and acronym.   Abstrak ___________________________________________________________________ Dalam kertas ini menjelaskan proses pembentukkan kata pada Gairaigo. Gairaigo adalah kata serapan bahasa Jepang yang berasal dari bahasa Asing selain bahasa China. Gairago mengalami penyesuaian bunyi (fonologi) dan penyusaian gramatikal sebelm dipinjam dan digunakan sebagai Gairaigo dalam bahasa Jepang. Gairaigo yang dianaisi adalah Gairaigo yang terdapat pada koran Yomiuri shinbun edisi 22 Januari 2017. Terdapat 2 proses yang terjadi pada Gairaigo yang ada pada sumber data. Pertama, proses Fonologi atau penyesuaian bunyi yang dibagi menjadi 5 aspek; penambahan vokal, pengubahan bunyi, aksen dan ucapan menurut ejaan dalam bahasa Jepang. Kedua, proses Morfologi atau morfem pembentuk kata. Proses morfologi dibagi menjadi 2 yaitu; Fukugo (penggabungan) dan Ryakugo (pemendekkan). Ryakugo terdiri dari singkatan, Clipping (pemenggalan) dan Akronim.